Essays on international trade and economics of conflict - Sellak, Manaf (Kansas State University, 2019)
The first chapter is motivated by the recent territorial disputes, in South China Sea and the Middle East, over external territories rich in natural resources. The objective of the study is to understand why political disputes over external territories sustain or persist despite that the countries engaged in conflict are trading partners. This chapter presents a game theoretical model to analyze the impact of bilateral trade on the economic and political behavior of the two contending countries. The analytical results suggest that greater trade openness (by lowering trade cost) reduces conflict intensity when the contending countries are symmetric in their national endowments. This finding is consistent with the liberal peace hypothesis that trade reduces conflict. For the case where there are differences in national resource endowments, the analysis shows that the overall conflict may increase despite greater trade openness. This chapter has policy implications on the role of bilateral trade and size of an economy for conflict resolution. The second chapter considers trade regionalism and the endogeneity of security policy. Using a sequential-move game, this chapter is the first to characterize the endogeneity of security and trade policies in a three-country framework with two adversaries and a neutral third party. It has been shown that an FTA between two adversaries (i.e., “dancing with the enemy” in trade regionalism) has the strongest pacifying effect, followed by worldwide free trade. Second, the pacifying effect of worldwide free trade is stronger than that of the protectionist regime. Third, relative to all other regimes, an FTA between one of the adversaries and a neutral third party is conflict-aggravating. Furthermore, this chapter compares conflict intensities when instead there is a customs union (CU) and identify differences in implications between CU and FTA for interstate conflicts. The third chapter investigates the scenario of two enemy countries that do not engage in trade. The objective is to analyze what would be their optimal arming allocations for national defense when a politically neutral third party forms a free trade agreement (FTA) with only one of the adversaries (Single FTA), as compared to the case when the third party forms an FTA with each of them (Multiple FTAs). The major finding is that an FTA between a neutral third country and each of the adversary countries (despite that they do not trade) has a pacifying effect since the overall conflict intensity decreases. However, an FTA between the third country and only one of the adversaries is conflict-aggravating as the overall conflict intensity increases.
Keywords: International Trade; Interstate Conflict; Regional Trade Agreements; Economics of Conflict; Security Policy; Trade Policy